Resilience and organisational empowerment among long‐term care nurses: effects on patient care and absenteeism. (3rd June 2015) - Williams, Jaime; Hadjistavropoulos, Thomas; Ghandehari, Omeed O.; Malloy, David C.; Hunter, Paulette V.; Martin, Ronald R.
Abstract : Aim: To study resilience among long‐term care (LTC) nurses and its relationship to organisational empowerment, self‐reported quality of care, perceptions of resident personhood (i.e. viewing another person as a person, implying respect) and absenteeism. Background: Although resilience has been examined among nurses, it has not been studied in LTC nurses where resident rates of dementia are high, and nurses may experience stress affecting care and the way residents are perceived. Method: A sample of one hundred and thirty LTC nurses from across North America completed a series of questionnaires. Results: Resilient nurses were more likely to report higher quality of care and to view residents as having higher personhood status (despite deteriorating cognitive function). Resilience was not predictive of absenteeism. Organisational empowerment did not add to the predictive power of resilience. Conclusions: Resilience is of importance in LTC nursing research and future studies could examine this construct in relation to objectively measured resident outcomes. Implications for nursing management: Our findings suggest that interventions to improve LTC staff resilience would be important to pursue and that consideration should be given to resilience in optimizing the match between potential staff members and LTC positions.